LA PLANEACIÓN ESTRATÉGICA COMO HERRAMIENTA PARA MEJORAR LA PRODUCTIVIDAD EN LAS AGENCIAS DE VIAJES Y TURISMO DE AREQUIPA - Mayurí Barrón, Jorge Vicente (2012)
The efficient management of theTravel & Tourism Agencies of Arequipa through the use of management tools such a sstrategic planning allows them to improve their productivity and at the present time that competitive pressure is strong forcing Travel Agencies and Tourism using best management techniques and failure to do so would bring a significant reduction of their competitiveness in the domestic and international markets. Of the 34 travel agencies and tourism were identified selected a total of 12 existing agencies in the city of Arequipa that use strategic planning as a business management tool, these agencies develop receptive tourism-related activities, and egresive or internal. From the study results demonstrated that 12 of the 34 Travel Agencies and Tourism Management Arequipa due to the constant use of the Strategic Planning, came to increase productivity.